Benefit‐to‐harm ratio of the Danish breast cancer screening programme. Issue 3 (10th May 2017) - Beau, Anna‐Belle; Lynge, Elsebeth; Njor, Sisse Helle; Vejborg, Ilse; Lophaven, Søren Nymand
Abstract : The primary aim of breast cancer screening is to reduce breast cancer mortality, but screening also has negative side‐effects as overdiagnosis. To evaluate a screening programme, both benefits and harms should be considered. Published estimates of the benefit‐to‐harm ratio, the number of breast cancer deaths prevented divided by the number of overdiagnosed breast cancer cases, varied considerably. The objective of the study was to estimate the benefit‐to‐harm ratio of breast cancer screening in Denmark. The numbers of breast cancer deaths prevented and overdiagnosed cases [invasive and ductal carcinoma in situ (DCIS)] were estimated per 1, 000 women aged 50–79, using national published estimates for breast cancer mortality and overdiagnosis, and national incidence and mortality rates. Estimations were made for both invited and screened women. Among 1, 000 women invited to screening from age 50 to age 69 and followed until age 79, we estimated that 5.4 breast cancer deaths would be prevented and 2.1 cases overdiagnosed, under the observed scenario in Denmark of a breast cancer mortality reduction of 23.4% and 2.3% of the breast cancer cases being overdiagnosed. The estimated benefit‐to‐harm ratio was 2.6 for invited women and 2.5 for screened women. Hence, 2–3 women would be prevented from dying from breast cancer for every woman overdiagnosed with invasive breast cancer or DCIS. The difference between the previous published ratios and 2.6 for Denmark is probably more a reflection of the accuracy of the underlying estimates than of the actual screening programmes. Therefore, benefit‐to‐harm ratios should be used cautiously. Abstract : What's new? Breast cancer screening reduces breast cancer mortality, but one negative side‐effect is overdiagnosis. Published estimates of the benefit‐to‐harm ratio–the number of prevented breast cancer deaths divided by the number of overdiagnosed breast cancer cases–vary considerably. This study reports a benefit‐to‐harm ratio of 2.6 for women invited to breast cancer screening in Denmark. Among 1, 000 invited women from age 50 and followed up until 79, 2–3 women would be prevented from dying from breast cancer for every overdiagnosed woman. International variations in benefit‐to‐harm ratios probably reflect differences in the accuracy of underlying estimates more than differences between screening programmes.